How Does ARBook Promotional Media For MSME Crafts Using Augmented Reality Marker Tracking Works? - Hermawan, Hardika Dwi; Noor, Zakky Muhammad; Ulfatun, Titik; Nonalisa, Septiarida; Saputri, Agatha; Yuliana, Irma (LPPM Universitas Bina Bangsa, 2021)
The present study aimed to develop a virtual book displaying Jogja craftwork using Augmented Reality (AR) technology as an interactive promotional media to advertise handicraft products originated from the Special Region of Yogyakarta.